Analisis Perbandingan Pendapatan Antara Penjualan Online Dan Offline Di Toko Uus Hasanah Hijab - Widadah, Sil Silatul; Aziz, Abd.; Syuhri, Saifuddin (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2024)
These technological advancements have led to dramatic changes in buying and selling habits. Promoting goods and services using online channels, such as social media and websites. This study aims to determine the comparison of online and offline sales revenue, and to determine the application of online and offline sales at the Uus Hasanah Hijab shop. The type of research used is field research, with a descriptive-qualitative approach. Data collection using observation, interviews, and documentation. The results of this study can conclude that online sales revenue is higher than offline sales, online sales reach 500 million, while offline sales are only 100 million. This happens because: 1) Offline sales transactions consumers must come directly to the store, while online can make transactions through various e-commerce platforms; 2) Offline operational costs are greater than online operations, because online only costs website maintenance and online marketing costs; 3) Offline reach and accessibility are limited to areas near the store, while online has a very wide range, anytime anywhere can transact; 4) Offline customer interactions can interact directly and can get product recommendations in person, while online interactions are only through communication media provided by each e-commerce platform such as WA, and the results of other customer reviews. Furthermore, the implementation of online sales for the Uus Hasanah Hijab shop uses several application platforms such as Instagram, Shopee, and TikTok. However, Uus Hasanah Hijab is more dominant in promoting Tiktok accounts compared to other online applications. Meanwhile, Uus Hasanah Hijab offline sales through making banners, distributing brochures, tidying up product displays, neat product packaging, imposing discounts and providing excellent service to customers who come to the Uus Hasanah Hijab Shop